A representação social da infância veiculada no desenho animado Hora de aventura - Silva, Bruna Tairine [UNESP] (2015)
This study, enrolled in the line of research Practices and Formative Processes in Education, had as main objective to identify and analyze the social representations explained in the TV cartoon Adventure Time about childhood and the specific objectives: to identify and analyze the preference of children on the TV cartoon; identify and analyze the social representation of childhood present in the television cartoon. The research has a qualitative approach with descriptive and explanatory design and for the effectiveness of data collection and this research, we used two instruments: a survey of 177 children, 30 children from a private school in the municipality of Diadema / SP and 147 children from a public school in São Bernardo Campo / SP in order to select which cartoon that prevailed in the preference of children and recording of children's programming selected for two months. Data analysis was based on content analysis. In seeking to identify the social representation of the cartoon about childhood, it is clear that he bears the image of a childhood that works with the ethical and moral issues, dealing with opposing values (good and evil), with feelings of friendship and love, facing conflicts without losing the fun and curiosity, as characteristics of children have a childhood marked by the multiplicity of cultures, concepts and core values to the process of learning and training. With this study, we intend to show the importance of researching the presence of the media on a day-to-day life of children, since they are present in all the places they frequent and can also be seen as a rich element for learning...